2012
DOI: 10.1182/blood-2011-10-385716
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29a and microRNA-142-3p are regulators of myeloid differentiation and acute myeloid leukemia

Abstract: IntroductionAcute myeloid leukemia (AML) is a heterogeneous group of blood cancers characterized by increased, uncontrolled proliferation of hematopoietic progenitors, and a blockage in myeloid differentiation is the major characteristic of AML. 1 According to the French-American-British classification system, AMLs involving the monocytic and granulocytic lineage account for 85% (M1 to M5 subtypes) of adult patients. 2 Under normal conditions, monocytes and granulocytes develop from long-term hematopoietic ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
156
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(170 citation statements)
references
References 45 publications
(51 reference statements)
9
156
1
1
Order By: Relevance
“…Prognostic value of miR-29a expression was especially more obvious in the subgroup of patients with intermediate risk cytogenetics 3 . This finding is consistent with the previous study showing reduced expression of miR-29a in adult AML patients 99 . In addition it was found that the decreased expression of miR-29a was significantly associated with classification subtype M7 (FAB) and the unfavorable cytogenetic risks 3 .…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Prognostic value of miR-29a expression was especially more obvious in the subgroup of patients with intermediate risk cytogenetics 3 . This finding is consistent with the previous study showing reduced expression of miR-29a in adult AML patients 99 . In addition it was found that the decreased expression of miR-29a was significantly associated with classification subtype M7 (FAB) and the unfavorable cytogenetic risks 3 .…”
supporting
confidence: 83%
“…It is conceivable that miR-29a and miR-142-3p promote myeloid differentiation primarily by affecting CCNT2, CDK6 and TAB2. Significantly increased levels of the target proteins were detected in the AML blast with abnormally reduced expression of miR-29a and miR-142-3p, which further suggested that these two miRNAs regulate myeloid differentiation and AML development via the three target genes 98,99 . Experimental data indicated that forced expression of miR-29a and miR-29b in AML cell lines and in primary AML blasts inhibited cell growth and induced apoptosis.…”
mentioning
confidence: 90%
“…Later studies using mouse and human cell lines have indicated that miR-142-3p is required for the development and function of terminally differentiated hematopoietic lineages, such as myeloid and dendritic cells. miR-142-3p can directly regulate the expression of tab2 in the myeloid lineage [22] and that of IL-6 in dendritic cells(DCs) [23]. Very recently, zebrafish miR-142-3p (ZFIN ID: ZDB-GENE-090929-151, miR-142a-3p herein) has been shown to be required for the maturation of primitive erythrocytes, cardiogenesis and vessel integrity [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…We considered that miR-29 family members may also play a role in osteoclastogenesis, given that altered miR-29 levels were associated with hematopoietic malignancies. For example, diminished miR-29 levels were found in patients with chronic lymphocytic leukemia and correlate with advanced clinical features and poor prognosis in acute myeloid leukemia (23)(24)(25)(26).…”
mentioning
confidence: 99%